Meningkatkan Hasil Belajar Pak Dalam Materi Pribadi yang Unik Menggunakan Model PBL (Problem Based Learning) dengan Media Video Youtube pada Kelas IV Fase B SD Joannes Bosco Kota Yogyakarta - Yulius Swantoro; Hartutik Hartutik (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
The learning method that has been applied in Grade IV at Joannes Bosco Elementary School Yogyakarta is less engaging. It affects the students’ performance. They show less cooperation. On the other hand, the expected achievement targets are not to be met. This research aims to improve the Gotong Royong dimension character and achievement targets through the implementation of a problem-based learning (PBL) model assisted by YouTube video media. This classroom action research was conducted in two cycles with the theme "My Unique Self," focusing on the sub-topics of strengths and weaknesses, and gratitude for uniqueness, with each cycle consisting of four stages: planning, action, observation, and reflection. The research subjects were 26 students of Grade IV, Phase B, at Joannes Bosco Elementary School Yogyakarta. The results showed an increase in the Gotong Royong dimension of the Pancasila Student Profile (P3) from 57% to 81% during the learning process using the PBL method. There was also an improvement in student learning outcomes, with the percentage of students achieving "proficient" increasing from 38% to 62%, "competent" remaining at 38%, and the categories "adequate" and "developing" decreasing from 19% and 4% to 0%, respectively. Overall, focusing on the Gotong Royong dimension using the PBL model assisted by YouTube videos proved effective in enhancing both the Gotong Royong character and learning achievement in Catholic Religious Education for Grade IV students at Joannes Bosco Elementary School Yogyakarta. It is suggested that teachers focus on one dimension in the character development process using methods that emphasize problem-solving.